2018
DOI: 10.1177/0269216318793286
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity and general health among family caregivers during end-of-life cancer care: A retrospective census survey

Abstract: Background:Family carers provide vital support for patients towards end-of-life, but caregiving has considerable impact on carers’ own health. The scale of this problem is unknown, as previous research has involved unrepresentative samples or failed to fully capture caregiving close to death.Aim:To quantify level of psychological morbidity and general health among a census sample of carers of people with cancer at end-of-life, compared to population reference data.Design:National 4-month post-bereavement posta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 36 publications
5
60
0
1
Order By: Relevance
“…The caregivers had worse overall MCS score than the general population sample, which is in line with previous findings that caregiving negatively affects the caregivers’ mental health. 23 26 Two of the previous studies used the SF-36 to assess mental health, 25 , 26 and our study confirmed poor mental health in caregivers in a prospective population-based study with a robust study design. Furthermore, we found that caregivers scored lower than the general population on all SF-36 mental health subscales.…”
Section: Discussionsupporting
confidence: 80%
“…The caregivers had worse overall MCS score than the general population sample, which is in line with previous findings that caregiving negatively affects the caregivers’ mental health. 23 26 Two of the previous studies used the SF-36 to assess mental health, 25 , 26 and our study confirmed poor mental health in caregivers in a prospective population-based study with a robust study design. Furthermore, we found that caregivers scored lower than the general population on all SF-36 mental health subscales.…”
Section: Discussionsupporting
confidence: 80%
“…Most older patients with cancer live at home and depend on informal caregivers for support with cancer treatment, symptom management, and activities of daily living . Clinicians often focus on the health of the patients, whereas informal caregivers are subjected to a significant amount of stress that can adversely affect their own physical and emotional health …”
mentioning
confidence: 99%
“…4,5 Clinicians often focus on the health of the patients, whereas informal caregivers are subjected to a significant amount of stress that can adversely affect their own physical and emotional health. [6][7][8] As the cancer progresses, the level of care burden increases for the caregiver and can profoundly worsen caregivers' quality of life (QOL). 9,10 The role of caregiving itself impacts the emotional health of the caregivers; many studies demonstrate that caregivers experience even more emotional health challenges (eg, anxiety, depression, distress) than the patients they are caring for.…”
mentioning
confidence: 99%
“… 4 , 5 Carers supporting palliative patients at home face substantial demands upon their time, and upon their mental and physical health. 6 – 9 In the coming decades, more people will be dying at home with increasingly complex care needs. 10 , 11 Recent European work has highlighted the need for family carers to be recognised as part of the ‘unit of care’, but carer support often occurs ad hoc rather than being systematic within health systems.…”
Section: Introductionmentioning
confidence: 99%